1987
DOI: 10.1515/dmdi.1987.5.4.273
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism and Biopharmaceutics of Spironolactone in Man

Abstract: Spironolactone, a competitive aldosterone antagonist, has been used for almost 30 years in those disorders associated with primary or secondary hyperaldosteronism. This review is confined to its metabolism and biopharmaceutics in man. Spironolactone undergoes extensive metabolism with no unchanged drug appearing in the urine. Its metabolites can be divided into two main categories: those in which the sulfur of the parent molecule is removed and those in which the sulfur is retained. The dethioacetylated metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 63 publications
1
25
0
3
Order By: Relevance
“…SL has poor aqueous solubility, which is about 2.8 mg/100 mL at 25°C. 28 A high amount of surfactant and Transcutol ® probably increased the solubility of SL in the aqueous phase; thus, the drug may suffer partition from the NLCs to the aqueous medium, causing a decrease in EE%.…”
Section: Effect Of Variables Effect Of Formulation Variables On the Pmentioning
confidence: 99%
“…SL has poor aqueous solubility, which is about 2.8 mg/100 mL at 25°C. 28 A high amount of surfactant and Transcutol ® probably increased the solubility of SL in the aqueous phase; thus, the drug may suffer partition from the NLCs to the aqueous medium, causing a decrease in EE%.…”
Section: Effect Of Variables Effect Of Formulation Variables On the Pmentioning
confidence: 99%
“…Spironolactone is rapidly metabolized in the liver into a number of metabolites including 7a-methyl-spironolactone and canrenone. Unchanged spironolactone, 7a-methyl-spironolactone, and canrenone all have anti-mineralocorticoid activities and their mean half-lives in normal subjects are 1.4, 13.8, and 16.5 h respectively (3,4). The onset of action of spironolactone is delayed with the peak response occurring several days after the first dose, possibly because, during continuous treatment, active metabolites reach steady-state plasma concentrations only slowly (4).…”
Section: Spironolactonementioning
confidence: 99%
“…Both spironolactone and 7 alphathiomethylspirolactone possess anti-mineralocorticoid activity. Concomitant food intake enhances the bioavailability of spironolactone by increasing its absorption and decreasing the fi rst-pass effect [ 211 ]. The Randomized Aldactone Evaluation Study (RALES), the fi rst major clinical trial of an ARA, reported that blockade of aldosterone receptors by spironolactone, in addition to standard therapy, substantially reduced the risk of morbidity and mortality among severe heart failure patients [ 212 ].…”
Section: Spironolactonementioning
confidence: 99%